HALP and SII: Innovative Biomarkers for Diagnosing Ovarian Cancer in Both Epithelial and Non-Epithelial Subtypes - Ridwan, Steven; Mantilidewi, Kemala Isnainiasih; A.W., Gatot Nyarumenteng; Kurniadi, Andi; Suardi, Dodi; Salima, Siti; Rauf, Syahrul; Hidayat, Yudi Mulyana (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: To evaluate the diagnostic utility of PHAL (Platelet, Hemoglobin, Albumin, and Lymphocyte), SII (Systemic Immune Inflammation Index), and SIRI (Systemic Inflammatory Response Index) for both epithelial and non-epithelial ovarian cancer.Methods: A cross-sectional study of 156 patients with ovarian masses was conducted using preoperative laboratory data to calculate PHAL, SII, and SIRI scores. Histopathology confirmed diagnoses. Population I included all ovarian cancer types and benign tumors, while Population II included only non-epithelial ovarian cancer and benign tumors. Statistical analysis using SPSS 25.0, involved ROC curve and validity testing to assess diagnostic performance.Result: SII showed the best performance in the overall population (AUC 0.738; sensitivity 71.25%; specificity 72.37%; accuracy 71.79%; LR+ 2.58; LR– 0.40). In the subgroup of non-epithelial ovarian cancer versus benign tumors, PHAL had the highest diagnostic accuracy (AUC 0.819; sensitivity 81.81%; specificity 73.68%; accuracy 75.51%; LR+ 3.11; LR– 0.25).Conclusion: PHAL and SII are effective, accessible, and low-cost biomarkers that can support ovarian cancer diagnosis through routine blood tests.PHAL dan SII: Biomarker Inovatif untuk Diagnosis Kanker Ovarium Subtipe Epitel dan Non-Epitel Abstrak Tujuan: Penelitian ini bertujuan untuk mengevaluasi nilai diagnostik dari PHAL (Platelet, Haemoglobin, Albumin, dan Limfosit), SII (Systemic Immune Inflammation Index), dan SIRI (Systemic Inflammatory Response Index) pada kanker ovarium epitelial dan non-epitelial. Metode: Penelitian dengan metode potong lintang ini melibatkan 156 pasien dengan massa ovarium. Data laboratorium pra-operatif digunakan untuk menghitung skor PHAL, SII, dan SIRI. Diagnosis ditegakkan melalui pemeriksaan histopatologi. Populasi I mencakup semua jenis kanker ovarium dan tumor jinak, sedangkan Populasi II hanya mencakup kanker ovarium non-epitelial dan tumor jinak. Analisis statistik dilakukan menggunakan SPSS 25.0, termasuk analisis kurva ROC dan uji validitas untuk menilai kinerja diagnostik. Hasil: Hasil penelitian menyimpulkan bahwa SII memiliki performa terbaik pada seluruh populasi (AUC 0,738; sensitivitas 71,25%; spesifisitas 72,37%; akurasi 71,79%; LR+ 2,58; LR– 0,40). Pada subkelompok kanker ovarium non-epitelial dibandingkan dengan tumor jinak, PHAL menunjukkan akurasi diagnostik tertinggi (AUC 0,819; sensitivitas 81,81%; spesifisitas 73,68%; akurasi 75,51%; LR+ 3,11; LR– 0,25). Kesimpulan: PHAL dan SII merupakan biomarker yang efektif, mudah diakses, dan berbiaya rendah yang dapat mendukung diagnosis kanker ovarium melalui pemeriksaan darah rutin. Kata kunci: Kanker ovarium, Skor PHAL (Platelet-Hemoglobin-Albumin-Limfosit), Systemic Immune-Inflammation Index, Systemic Inflammatory Response Index